2012
DOI: 10.1242/jcs.093229
|View full text |Cite
|
Sign up to set email alerts
|

Altered nanofeature size dictates stem cell differentiation

Abstract: SummaryThe differentiation of stem cells can be modulated by physical factors such as the micro-and nano-topography of the extracellular matrix. One important goal in stem cell research is to understand the concept that directs differentiation into a specific cell lineage in the nanoscale environment. Here, we demonstrate that such paths exist by controlling only the micro-and nano-topography of polymer surfaces. Altering the depth (on a nanometric scale) of micro-patterned surface structures allowed increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 38 publications
3
77
0
Order By: Relevance
“…The authors provided further evidence that differentiation of skeletal stem cells cultured on nanotopographical surfaces, provided an equal and effective technique of differentiation of stem cells compared to chemical induction [33] . Zouani et al [34] similarly showed that hMSCs cultured on polyethylene terephthalate substrates with nano-depths of varying degrees, had higher osteogenic differentiation on the 100 nm patterns compared to the 10 nm patterns. The organization of the hMSCs on the 100 nm was believed to induce FA contacts, generating stress in the actin filaments.…”
Section: Surface Topographical Cluesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors provided further evidence that differentiation of skeletal stem cells cultured on nanotopographical surfaces, provided an equal and effective technique of differentiation of stem cells compared to chemical induction [33] . Zouani et al [34] similarly showed that hMSCs cultured on polyethylene terephthalate substrates with nano-depths of varying degrees, had higher osteogenic differentiation on the 100 nm patterns compared to the 10 nm patterns. The organization of the hMSCs on the 100 nm was believed to induce FA contacts, generating stress in the actin filaments.…”
Section: Surface Topographical Cluesmentioning
confidence: 99%
“…The organization of the hMSCs on the 100 nm was believed to induce FA contacts, generating stress in the actin filaments. Actin tension was found to be important in the osteogenic differentiation of the cells as the osteoblastic phenotype was inhibited by cytochalasin D [34] . …”
Section: Surface Topographical Cluesmentioning
confidence: 99%
“…When ESCs are aggregated into embryoid bodies (EB), which mimic early stages of embryonic development, it becomes clear that geometrical signals also affect cell-cell interaction and hence guide stem cell differentiation [66]. The investigation of hexagonal patterns, random nanopits, disordered and ordered squares utilising on hMSCs electron beam lithography (EBL) showed that highly asymmetric structures resulted in highest osteogenic expression in the absence of growth factor supplemented medium [237] indicating that nano-sized topographical induction of stem cell differentiation is as effective as chemical induction [238]. Micropatterns have also been shown to affect cell shape.…”
Section: Topographical Signals As Regulators Of Stem Cell Fatementioning
confidence: 99%
“…26 Previous studies have shown that adhesion, migration, and proliferation of MSCs as well as their differentiation into osteoblasts are all strongly dependent on surface topography at the nanoscale. 50, 51 Dalby et al reported that randomly placed nanotopographies were able to induce osteogenic differentiation of MSCs. 52 Osteoblastic differentiation markers, including alkaline phosphatase activity, osteocalcin expression, and mineralization, were measured in the present study to validate the effect of nanoporous alumina on osteogenic differentiation of MSCs in induction medium.…”
Section: Figurementioning
confidence: 99%